CLASSROOM TECHNIQUES USED BY THE TEACHER TO DEVELOP STUDENTSâ ENGLISH SPEAKING SKILL: A NATURALISTIC STUDY - Febriyanti, Reny Mirza (JoLLIET, 2016)
This research describes types of technique used by the English teacher of SMA N2 Sukoharjo to develop studentsâ English speaking skill, the purposes of eachtechnique, teacherâs roles, studentâs roles, and instructional material. The type ofthis research is descriptive qualitative especially Naturalistic. Methods used inthis research are: observation, interview, filed note, and documentation. Theresult shows that the type of technique used by the English teacher in teachinglearning process to develop studentsâ speaking skill at SMA N 2 Sukoharjo suchare Group Work Presentation, Drama, and Song. Teacherâs roles in teachinglearning process such as teacher as a Controller, as a Prompter, as an Assessor, asan Organizer, as an Observer, and as an Model. Studentâs roles in teachinglearning process such are student as a Planner, as a Member, and as a Tutor.Material used by the English teacher in teaching learning process is âBahasa danSastra Inggris: Peminatan Ilmu Bahasa dan Budayaâ written by Hidayat, et.al(2013). The conclusion in this research is the English teacher at SMA N 2Sukoharjo used various techniques to develop studentsâ speaking skill in teachinglearning process. Various techniques used by the teacher in teaching learningprocess make the student more active, more creative and the student moreenthusiastic in teaching learning process especially in speaking activity in theclassroom. Various techniques also make the student not bored when learningprocess, the studentsâ fun, enjoyed and confident when learning speaking process.Based on the observation, the use of technique in teaching learning process isvery important to make situation in classroom more interesting and make thestudent enthusiastic in learning process.Key words: Classroom Technique in Teaching Speaking, Instructional Material,Studentâs and Teacherâs Roles